Wehousebelda: Learning Management System as Online Learning Media at Universitas Muhammadiyah Parepare - Henra Ahmad,; Dirman Sudirman, (Edumaspul: Jurnal Pendidikan, 2026)
The research proposed to be funded with the title Wehousebelda: Learning Management System as an Online Learning Media at Universitas Muhammadiyah Parepare has a long-term goal of finding a Blended Learning Formulation on an online basis using LMS (Learning Management System Wehousebelda UMPAR) which can later be integrated with Virtual and Augmented Reality. To achieve the long-term goals of this research, the initial stage of research this year will focus on the use of Wehousebelda. Students have the perception of being able to learn and use the Wehousebelada LMS easily. Students have the perception that the Wehousebelda LMS is easier to use when compared to other online applications used by lecturers. The features provided on the Wehousebelda LMS are easy for students to understand and use. The Wehousebelda LMS really supports students as a tool in collecting assignments and accessing assignments again anywhere and at any time. Students' perceptions state they have sufficient time to access the Wehousebelda LMS to study and submit assignments. Student perceptions stated that they preferred to continue using the Wehousebelda LMS for studying and submitting assignments in the following semesters. Student perceptions of the Wehousebelda LMS are very positive, in this case, the LMS supports online learning, especially in ICT-based learning media courses.